ERV14 receptor impacts mycelial growth via its interactions with cell wall synthase and transporters in Aspergillus niger - Zheng, Junwei; Yao, Linlin; Zeng, Xu; Wang, Bin; Pan, Li (Frontiers in Microbiology, 2023)
Efficient protein secretion is closely correlated with vesicle sorting and packaging, especially with cargo receptor-mediated selective transport for ER exit. Even though Aspergillus niger is considered an industrially natural host for protein production due to its exceptional secretion capacity, the trafficking mechanism in the early secretory pathway remains a black box for us to explore. Here, we identified and characterized all putative ER cargo receptors of the three families in A. niger. We successfully constructed overexpression and deletion strains of each receptor and compared the colony morphology and protein secretion status of each strain. Among them, the deletion of Erv14 severely inhibited mycelial growth and secretion of extracellular proteins such as glucoamylase. To gain a comprehensive understanding of the proteins associated with Erv14, we developed a high-throughput method by combining yeast two-hybrid (Y2H) with next-generation sequencing (NGS) technology. We found Erv14 specifically interacted with transporters. Following further validation of the quantitative membrane proteome, we determined that Erv14 was associated with the transport of proteins involved in processes such as cell wall synthesis, lipid metabolism, and organic substrate metabolism.